2020
DOI: 10.1186/s13054-020-2793-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of septic shock in patients with candidemia: a post hoc analysis from two prospective cohorts

Abstract: Background: Almost one third of the patients with candidemia develop septic shock. The understanding why some patients do and others do not develop septic shock is very limited. The objective of this study was to identify variables associated with septic shock development in a large population of patients with candidemia. Methods: A post hoc analysis was performed on two prospective, multicenter cohort of patients with candidemia from 12 hospitals in Spain and Italy. All episodes occurring from September 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
0
22
0
3
Order By: Relevance
“…Presence of a CVC, malignancy on chemotherapy or previous chemotherapy, parenteral nutrition, recent surgery and recent antibiotic use were highly prevalent in patients with K ohmeri fungemia, implicating these factors as important risks. Importantly, these factors have been repeatedly identified to predispose to other invasive mycoses as well 23,42,47–49 . Indeed, since Candida species and K ohmeri belong to the same family, it is not of surprise that they share common properties regarding pathogenicity; thus, having common predisposing factors for invasive fungal infection was not an unexpected finding 48 …”
Section: Discussionmentioning
confidence: 98%
“…Presence of a CVC, malignancy on chemotherapy or previous chemotherapy, parenteral nutrition, recent surgery and recent antibiotic use were highly prevalent in patients with K ohmeri fungemia, implicating these factors as important risks. Importantly, these factors have been repeatedly identified to predispose to other invasive mycoses as well 23,42,47–49 . Indeed, since Candida species and K ohmeri belong to the same family, it is not of surprise that they share common properties regarding pathogenicity; thus, having common predisposing factors for invasive fungal infection was not an unexpected finding 48 …”
Section: Discussionmentioning
confidence: 98%
“…Adherence to the candidemia guideline [ 1 ] was measured by calculation of The European Confederation of Medical Mycology Quality of Clinical Candidemia Management score (EQUAL Candida score) [ 13 ]. The source of candidemia was classified based on clinical evidence of infection using the definition from a previous study [ 14 ]. Outcomes of candidemia were assessed in the followings: (1) mycological response defined as eradication of candidemia resulted in negative blood culture (mycological failure defined as a failure to eradicate candidemia); (2) 30-day mortality defined as death within 30 days after the first positive blood culture for candidemia.…”
Section: Methodsmentioning
confidence: 99%
“…As the values of R 2 and Q 2 approach 1, the model theoretically becomes better with worse fitting accuracy. In general, R 2 and Q 2…”
Section: Resultsmentioning
confidence: 99%
“…Candida albicans, Candida tropicalis, and Candida krusei have high incidence rates in the clinic. 2 The incidence rate of C. albicans is the highest among Candida species; however, a 5-year study by Barchiesi et al in Italy showed that the mortality rate of non-C. albicans and that of C. albicans are similar. It even tends to exceed the mortality of C. albicans.…”
Section: Introductionmentioning
confidence: 98%